ANALISIS KINERJA AUDITOR INTERNAL DALAM MENDETEKSI KECURANGAN KREDIT FIKTIF PADA KOPERASI SIMPAN PINJAM (KSP) ARTA NIAGA MAKASSAR (Lembaga Pengembangan Kinerja Dosen, 2022)
The business activity of savings and loan cooperatives is the collection and distribution of funds in the form of lending, especially from and for members. In its development, savings and loan cooperatives serve not only members but also the wider community. Savings and loan cooperatives were established to provide the opportunity for its members to obtain loans with ease and low interest rates. The purpose of this study was to determine the performance of internal auditors in detecting fictitious credit fraud at KSP Arta Niaga Makassar. The research method is descriptive qualitative, data analysis techniques used are data reduction or data simplification, data exposure or presentation, and drawing conclusions. The results of the study are 1) Auditors are expected to be able to detect fraud better because so far the ability of the Arta Niaga Makassar Savings and Loans Cooperative (KSP) has not been maximized in overcoming fictitious credit fraud. 2) The Arta Niaga Makassar Savings and Loans Cooperative (KSP) must be able to control fraud in detecting fictitious credit by maximizing fictitious credit.